Plato on virtue and the law - Berges, Sandrine (Continuum studies in ancient philosophy., 2009)
Ancient philosophy is no longer an isolated discipline. Recent years have seen the development of a dialogue between ancient and contemporary philosophers writing on central issues in moral and political philosophy. The renewed interest in character and virtue as ethical concepts is one such issue, yet Plato's contribution has been largely neglected in contemporary virtue ethics. In Plato on Virtue and the Law, Sandrine Berges seeks to address this gap in the literature by exploring the contribution that virtue ethics make to the understanding of laws alongside the interesting and plausible i.